(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Plants are both a source of food and resource for mankind. In country like India, plants have a wide application keeping in mind the agricultural and medicine research area. Out of several thousands of classes of medicinal plants, few may get vanished soon due to global warming, lack of knowledge of different species and several other diseases. Plants assume a significant job in human life being one of the critical variables of natural way of life; on the other hand couples of them are toxic and harmful to mankind as well. Thus, protecting the plants with medicinal and food values, as well as identifying the unknown species of the plants is the need of an hour. The study of plants classification with the help of different features of the leaf can be done in order to build an ideal database for the farmers and professional botanist. This could also serve for the automatic plant leaf disease detection system. The loss of crops as well as plants with medicinal values due to diseases is of the core concern to plant security. It is utmost important to design the essential infrastructure for the detection of the diseases that are observed in plant leaves. An optimal system for plant leaf detection can further guide for remedial solution. This work reviews different methodologies for plant leaf detection, its classification and detection of plant leaves diseases. Swarm Intelligence based techniques impressively address the real time optimization problems which motivates the further research work.